QARAQALPAQ BALALAR DRAMATURGIYASÍNÍŃ PAYDA BOLÍWÍNDA XALÍQ AWIZEKI ÁDEBIYATÍNÍŃ TUTQAN ORNÍ - Ataniyazova, G. (SCIENCE and SOCIETY, 2024)
This article provides insights into the emergence of Karakalpak children's drama in the works of folk literature. It explores elements of drama in folktales, epics, short stories, novellas, proverbs, oratory, terme-tolga (traditional sayings), children's presentation with spoons, moving moon, and presents question-and-answer genres of monologue-dialogue.